PEMERIKSAAN KESEHATAN DAN PENGOBATAN PENYAKIT MELALUI BAKTI SOSIAL DI DESA CIKEAS UDIK KABUPATEN BOGOR - Liana, Duta; Maratis, Jerry; Fauziah, Nuraini; Anggrani, Santi; Ulli, Meilandna; Hendrawan, Suwanda; Putri, Yunita Eka; Utomo, Haryo Setyo (Jurnal Abdi Insani, 2025)
Non-communicable diseases (NCDs) and infectious diseases are still challenging public health problems. The increase of prevalence directs need for community preventive and promotive to behave healthily and change their lifestyle. In supporting tri dharma and improving public health, community service was carried out as social services and treatment in Cikeas Udik Village. This activity aims to determine description of disease, provide counseling and education, and provide social services and health treatment to community. Activity steps include counseling, screening examinations, and treatment. Univariate data analysis used descriptive. Number of participants was 94 people, of which 82% were women. The examination results showed that the patient's blood pressure was normal, but hypertension was the highest diagnosis. Laboratory examination results showed normal GDS, normal cholesterol, abnormal uric acid in women. There are five largest drug groups, namely analgesics, antihypertensives, antidiabetics, antacids, and multivitamins. Then the body balance of the community still needs to be inhanced. It can be concluded that social service provide benefits to the people. Participants are very enthusiastic in the activities. It is hoped that health conditions will be known, have good and appropriate treatment will be obtained.